ANALISIS KOMITMEN KARYAWAN TERHADAP PENERAPAN SISTEM MANAJEMEN K3 (SMK3) - Nuriati Dewi; Susilawati Susilawati (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2023)
The Occupational Safety and Health Management System (SMK3) is part of the company's overall management system in order to control risks related to work activities in order to create a safe, efficient and productive workplace (PP No. 50 of 2012). Occupational Safety and Health (K3) are all activities to guarantee and protect the safety and health of workers through efforts to prevent work accidents and work-related diseases. Companies or organizations that will or have implemented SMK3 are expected to be able to increase the effectiveness of planned, measurable, structured and integrated occupational safety and health protection, then be able to prevent and reduce work accidents and work-related illnesses by involving elements of management and workers, and also companies can create a safe, comfortable and efficient workplace to boost productivity. This research method uses the method of collecting data in this study using the literature review method (literary study).